J-E characteristics of Ni-catalysed multiwalled carbon nanotubes. (10th August 2009) - Khan, Zishan H.; Khan, Samina; Husain, M.; Salah, Numan; Habib, Sami; Khan, Shamshad
A catalytic decomposition of hydrocarbons involving N2, C2H2 and H2 gas mixtures is used to synthesise the Ni catalysed carbon nanotubes (CNTs). These CNTs are grown on nanocrystalline film of nickel using low-pressure chemical vapour deposition (LPCVD). During the synthesis of these nanotubes, the growth temperature and growth time is kept at 700°C and 30 minutes respectively. The pressure in LPCVD chamber is maintained at 10 Torr. FESEM and HRTEM are employed to study the growth mechanism of these as grown CNTs. FESEM images suggest that these CNTs are very long and their diameter varies from 10-50 nm. It is also confirmed from HRTEM image that these nanotubes are multiwalled with the diameter varying from 10-50 nm and length of several micrometers. It is clear from SEM mage that the inner and outer tube diameter of these CNTs is 5 nm and 12 nm respectively. On the basis of J-E characteristics, it is observed that these multiwalled carbon nanotubes (MWNTs) show a turn-on field of 6.23V/μm, when the current density achieves 5μA/cm2 and the field enhancement factor is estimated to be 5.41 × 10 6cm−1.